Integrasi Pendekatan Sains, Teknologi, dan Nilai Islam dalam Pembelajaran Akidah Akhlak - Sukmayeti, Sukmayeti; Alrasi, Fitri; Masnita, Delmi; Nurhamidar, Nurhamidar; Wahyuni, Yessi (TSAQOFAH, 2026)
The rapid development of science and technology has had significant implications for educational practice, including in Akidah Akhlak instruction, thereby necessitating efforts to balance intellectual strengthening with the moral and spiritual development of students. This article aimed to analyze the integration of scientific, technological, and Islamic value-based approaches in Akidah Akhlak learning as a holistic instructional strategy. This study employed a library research method by analyzing various relevant sources, including books, journal articles, and scientific documents. The findings show that integrating science into Akidah Akhlak learning can strengthen students’ faith by linking scientific phenomena with the greatness of Allah SWT, while the use of educational technology contributes to creating a learning process that is more interactive, contextual, and aligned with the characteristics of students in the digital era. These findings affirm that the integration of science, technology, and Islamic values plays an important role in shaping students who are faithful, knowledgeable, and of noble character. Thus, such integration is not only a pedagogical necessity but also a strategic paradigm for realizing Islamic education that is holistic and adaptive to contemporary developments.